La pandemia de covid-19 en municipios afromexicanos de la costa guerrerense y oaxaqueña = The covid-19 pandemic in the Afro-Mexican municipalities on the Guerrero and Oaxaca coast; The COVID-19 pandemic in the Afro-Mexican municipalities on the Guerrero and Oaxaca coast - Berrio Palomo, Lina Rosa (Universidad Autónoma Metropolitana)
La pandemia de covid-19 ha transformado la vida de las personas en todo el mundo, pero presenta particularidades en cada contexto. Este artículo analiza algunos de sus efectos en cinco municipios afromexicanos en la costa de Guerrero y Oaxaca. Con datos oficiales de salud y entrevistas realizadas por investigadoras locales, se desarrolló un estudio colaborativo sobre la situación de los contagios en la región, las redes de servicios disponibles para su atención y la percepción de riesgo por parte de la población. Los hallazgos muestran la incertidumbre frente al virus y –aunque la prevalencia de contagios aparentemente es baja— la pandemia ha visibilizado las precarias condiciones socioeconómicas y de infraestructura en salud, así como las vulnerabilidades estructurales en una región con altos índices de marginación. Es un estudio exploratorio que analiza los primeros meses de la pandemia, pero aporta a su comprensión en contextos rurales y entre la población afromexicana.; The covid-19 pandemic has transformed people’s lives globally but has particularities specific to each context. This article analyzes some of its effects in five Afro-Mexican municipalities on the coast of Guerrero and Oaxaca. Using official health data and interviews conducted by local researchers, we developed a collaborative study about the situation of infections in the region, the service networks available for their care, and the perception of risk by the population. The results show the uncertainty regarding the virus and –even though the prevalence of infections is apparently low– the pandemic has exposed the precarious socioeconomic and health infrastructure conditions and the structural vulnerabilities in a region with high rates of marginalization. It is an exploratory study that analyzes the first months of the pandemic but contributes to its understanding in rural contexts and among the Afro-Mexican population.